Multilayered Approach to Archaeological Research in the Urban Environment - Case Study: Siscia - Miloglav, Ina (Array, 2013)
The complex architectural history, surface and underground infrastructure of modern towns demand suitably adjusted strategy for archeological and geophysical research. Archaeological sites Sr. Quirinus and St. Cross, more or less successfully open »time windows« through the modern urban tissue to the remains of Roman town of Siscia. Archaeological and geophysical research has confirmed that the area of St. Quirinus with the remains of public buildings, monumental city gate, street pattern and parts of the city wall is considered an ideal example of developed Roman urbanism to be presented to the public as an open Archaeological park.